2017
DOI: 10.3389/fped.2017.00043
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Akt/mTOR Signaling in Children with Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a behaviorally defined disorder affecting 1 in 68 children. Currently, there is no known cause for the majority of ASD cases nor are there physiological diagnostic tools or biomarkers to aid behavioral diagnosis. Whole-genome linkage studies, genome-wide association studies, copy number variation screening, and SNP analyses have identified several ASD candidate genes, but which vary greatly among individuals and family clusters, suggesting that a variety of genetic mutations m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 68 publications
2
51
0
1
Order By: Relevance
“…Because all these effects were blocked by rapamycin, it was suggested that they occur through the mTORC1 pathway hyperactivation [27]. However, a shift toward higher Akt/mTOR activity has been demonstrated for the general ASD population and not limited to known ASD-associated mTOR pathway genetic mutations [8]. In this study, we reported that 349 out of 1053 SFARI genes ( Supplementary Table S3) were directly associated with the mTORC1 pathway, part of them belongs to it, while others depend on it in their translation.…”
Section: Discussionmentioning
confidence: 99%
“…Because all these effects were blocked by rapamycin, it was suggested that they occur through the mTORC1 pathway hyperactivation [27]. However, a shift toward higher Akt/mTOR activity has been demonstrated for the general ASD population and not limited to known ASD-associated mTOR pathway genetic mutations [8]. In this study, we reported that 349 out of 1053 SFARI genes ( Supplementary Table S3) were directly associated with the mTORC1 pathway, part of them belongs to it, while others depend on it in their translation.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model of fragile X syndrome, a disorder also with elevated GSK-3β activity and associated with significant cognitive impairments [55,56], increased HIP theta was evident [57], and in autism, there is a higher relative EEG theta in autistic youth [58,59], or a greater theta/beta frequency ratio [59]. Yet, it is noteworthy that although GSK-3β has recently emerged as a potential signaling hub in autism [5], evidence indicates protein activity may actually be downregulated [6][7][8]. This raises the possibility that GSK-3β may play a more homeostatic role in brain systems function, with aberrant up or downregulation in protein activity having consequent negative effects on cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen synthase kinase-3β (GSK-3β) is a serine/threonine kinase with over 100 biological substrates [1] that has been repeatedly shown to play a critical role in the pathology of various neuropsychiatric and neurodegenerative diseases, and in particular those that present with cognitive dysfunction [2][3][4][5]. Whereas decreased GSK-3β activity has been implicated in autism [6][7][8], most often disorders of cognitive dysfunction are associated with increased activation of the kinase, the most widely studied being Alzheimer's disease (AD) [2,9,10]. GSK-3β expression and/or activity levels are elevated in the hippocampus (HIP) and prefrontal cortex (PFC) [11][12][13], and this finding is mimicked in animal model systems used to study the disease [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, given its complex nature(78, 79), which includes crosstalk with other signaling pathways and the presence of feedback loops, it is difficult to state whether the observed results are indicators of pathway activation or inhibition. Interestingly, ASD idiopathic cases and monogenic diseases related to autism have been linked to both higher and lower activity of the PI3K/AKT/MTOR axis(8082). The PI3K/AKT/MTOR axis is one the most frequently altered pathways in human tumors and directly participates in the regulation of many cancer hallmarks(83).…”
Section: Discussionmentioning
confidence: 99%